2003
DOI: 10.1037/h0086959
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Canadian Psychologists in Conducting Fitness and Criminal Responsibility Evaluations.

Abstract: Historically, only physicians, typically psychiatrists, were permitted to conduct forensic mental health evaluations for the courts. In the United States, the courts have affirmed increasing acceptance of involvement of psychologists since the 1940s. In Canada, the legal system continues to adhere to the assumption of medical dominance to a large extent. For instance, Canadian legislation requires that a physician conduct court-ordered assessments of fitness to stand trial and criminal responsibility. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…Ultimately, there were no changes to the CCC in terms of the inclusion of psychologists in fitness to stand trial and criminal responsibility assessments. Viljoen, Roesch, Ogloff, and Zapf (2003) reviewed the role of Canadian psychologists in fitness to stand trial and criminal responsibility evaluations. Based on a review of empirical literature and case law, they concluded that psychologists were qualified to conduct these types of evaluations.…”
mentioning
confidence: 99%
“…Ultimately, there were no changes to the CCC in terms of the inclusion of psychologists in fitness to stand trial and criminal responsibility assessments. Viljoen, Roesch, Ogloff, and Zapf (2003) reviewed the role of Canadian psychologists in fitness to stand trial and criminal responsibility evaluations. Based on a review of empirical literature and case law, they concluded that psychologists were qualified to conduct these types of evaluations.…”
mentioning
confidence: 99%
“…This is not surprising considering that students need to become familiar with the legislation in their country, and understand the applications of the law and the workings of the criminal justice system. This increased focus is notable considering that insufficient legal knowledge has been a source of criticism against psychologists and psychiatrists conducting forensic evaluations (Viljoen et al, 2003). Many scholars agree that this component is essential in the training of forensic psychologists (Burl et al, 2012; DeMatteo et al, 2009; Heilbrun, 2001) and should includefoundations of the legal system, sources of law, legal research, relevant civil and criminal case law, criminal and civil procedures relevant to forensic practice, legal rules and professional guidelines relating to expert testimony, and substantive law in relevant areas (e.g., competence to stand trial, mental state at the time of the offense).…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists are also becoming progressively more involved in aspects of forensic mental health assessments of different types, including those that have been historically dominated by psychiatrists (Canadian Psychological Association, 2017; Gowensmith, Pinals, & Karas, 2015; Pillay, 2014; Viljoen, Roesch, Ogloff, & Zapf, 2003). This is an important shift, considering that clinical psychologists, in particular, are trained in forensic mental health evaluations.…”
mentioning
confidence: 99%
“…Pillay and others have argued that the pool of evaluators be expanded to include clinical psychologists and psychiatrists (Large et al, 2009; Pillay, 2014). Historically, forensic mental health evaluations in the United States were restricted to the purview of psychiatrists or medical doctors only (Perlin, 1977; Viljoen, Roesch, Ogloff, & Zapf, 2003). However, the past several decades have seen a gradual expansion in the qualifications of eligible evaluator disciplines.…”
Section: Solutions To Datementioning
confidence: 99%